Nurses' Experience in Providing Excellent Service to Patients Very Important Person at Panti Nirmala Hospital - Antina Atik; Katmini (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
Service is the best service provided by hospital employees to meet or even exceed the expectations of hospital service users. With the increasing demands of patients and families, hospitals must provide quality, fast, and professional services, especially for nurses who are 24 hours with patients. Excellent service is needed because it has an impact on patient and family satisfaction. The purpose of this study was to explore the experiences of nurses in providing excellent service to VIP patients at Panti Nirmala Hospital. This phenomenological qualitative study involved 15 nurses who worked in the VIP room, the sampling technique used purposive sampling to select informant according to the inclusion criteria of the nurses in the VIP room who had more than 5 until 10 years of experience, were able to communicate and speak Indonesian and were willing to become informant. The data were collected by in-depth interviews for 30-60 minutes with the researcher as the main instrument. The transcribed interview results were analyzed using thematic analysis techniques. The results obtained 6 themes, namely the character of VIP patients facilitating the assessment process, the patient's critical thinking pattern requires nurses to be more careful in implementing actions, active client communication patterns require nurses to be more communicative, nurses are required to look attractive, nurses are required to provide excellent service, and the complexity of the challenges in caring for VIP patients. In the application of nursing care to VIP patients, nurses are required to provide more performance and improve therapeutic communication. And it is suggested that in improving the quality of nursing services, it is necessary to increase cognitive abilities and soft skills related to service excellence.